The autobiographical documentary: archive and montage to represent the self. Issue 3 (2nd September 2021) - Rosas, Vladimir; Dittus, Rubén
ABSTRACT: This essay aims to examine how archival material is repurposed within autobiographical documentaries in order to reconstruct the documentarian filmmaker's self in relation to their family. It is plausible for the filmmaker to explore their own identity by reexamining their family history, especially with interviews and observational devices; however, domestic media plays a particular role in creating a supporting discourse that finds new meanings from the confrontation of statements and images. By analyzing three examples of autobiographical documentaries, namely Tarnation (Jonathan Caouette, 2003), 51 Birch Street (Doug Black, 2005) and The Marina Experiment (Marina Lutz, 2009), we will explore how the re-contextualization of personal images works as a narrative strategy to unveil identity contestations in American autobiographical filmmaking.